The Effect of Financial Targets and Financial Stability on Fraudulent Financial Reporting With The Audit Committee As a Moderation - Krisna Monica, Ni Kadek Dela; Purnamawati, I Gusti Ayu; Werastuti, Desak Nyoman Sri (Dinasti Publisher, 2025)
This study aims to determine several influencing variables, namely: (1) Financial Targets, (2) Financial Stability, Against Financial Report Fraud moderated by the Audit Committee variable. The population used in this study is the infrastructure sector companies listed on the Indonesia Stock Exchange in 2021-2023. Sampling using purposive sampling technique. The data collection method used is documentation, namely data obtained in the form of annual reports of each issuer of infrastructure sector companies listed on the Indonesia Stock Exchange in 2021-2023 and the literature study method is also applied by analyzing and analyzing various sources of literature related to this study. This research employs logistic regression analysis, with data processing conducted using the STATA software. The findings indicate that financial targets exert a significant negative impact on Financial Report Fraud, Financial Stability has a positive and significant effect on Financial Report Fraud, the Audit Committee weakens the negative effect of the influence of Financial Targets on Financial Report Fraud, the Audit Committee weakens the positive effect of Financial Stability on Financial Report Fraud.